The Party's Over Frederick Ashton, the Royal Ballet's founder choreographer celebrated - Craine, Debra (Dance Books Ltd., Alton,Hampshire (UK), 2005)
The Royal Ballet's founder choreographer celebrated. PALABRAS CLAVE: Royal Ballet, Month in the Country, Symphonic Variations, Frederick Ashton.